Music of the Baduy People of Western Java Singing is a Medicine - van Zanten, Wim (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2020)
Music of the Baduy People of Western Java: Singing is a Medicine by Wim van Zanten is about music and dance of the indigenous group of the Baduy, consisting of about twelve-thousand people living in western Java. It covers music for rice rituals, for circumcisions and weddings, and music for entertainment. The book includes many photographs and several discussed audio-visual examples that can be found on DOI: 10.6084/m9.figshare.c.5170520. Baduy are suppposed to live a simple, ascetic life. However, there is a shortage of agricultural land and there are many temptations from the changing world around them. Little has been published on Baduy music and dance. Wim van Zanten's book seeks to fill this lacuna and is based on short periods of fieldwork from 1976 to 2016. Readership: Ethnomusicologists and anthropologists, especially those interested in ethnic minority groups. It is also meant for scholars, NGOs and administrators of intangible cultural heritage and people of Baduy descent.